Utilizing SIOP lesson video demonstrations as a springboard for reflection: A collaborative self-study of EL teachers. Issue 3 (3rd July 2021) - Riley, Jacqueline; Babino, Alexandra
Abstract: This collaborative self-study explored three graduate students' perceptions of the benefits and challenges of viewing, editing, and sharing lesson demonstrations based on Sheltered Instruction Observation Protocol (SIOP). The researchers also examined how university instructors could promote reflection through the lesson demonstration process. The study consisted of four qualitative forms of data collection. First, the researchers interviewed participants regarding their experiences viewing, editing, and sharing their videos. Then, they examined participants' written reflections of their lesson demonstration, focusing on best practices for teaching English learners (ELs). Using the constant comparative method, they coded the interview transcripts, participant reflections, and instructor feedback. Researchers performed a document analysis of course materials (e.g., instructions, rubrics, lesson plan templates) to better understand and contextualize participants' perceptions of the lesson demonstration process within the course. The findings indicated that participants benefited from the process in a variety of ways, while experiencing minimal or no challenges. In reviewing and editing the footage, participants expressed how they were able to view their teaching from a new vantage point and identify unique opportunities for future growth from other professional development strategies. Due to participants' limited sharing of the video, this stage of the process was not fully explored.